The potential of airborne synthetic aperture radar (SAR) imagery as a basic tool for stratigraphic investigations in forested areas: The Ordovician-Silurian carbonate succession of Anticosti Island, Gulf of St Lawrence, eastern Canada - Gauthier, Eric L (University of Ottawa (Canada), 2003)
Anticosti Island, located in the Gulf of St. Lawrence in eastern Canada, is one of the few places in the world where the Ordovician/Silurian boundary is well preserved and exposed. Its relatively undeformed shallow-water carbonate sequence of approximately 900 m in thickness is rich in fossils and is known to contain traces of hydrocarbons. The island has been for decades the subject of several geological studies, but its stratigraphic succession was never successfully mapped precisely because of its dense forest cover present over almost 95% of its vast territory. This study provides new mapping tools and techniques to support the geological representation of the island stratigraphic succession. Airborne SAR (Synthetic Aperture Radar) data acquired with the active radar system onboard of the former CCRS (Canada Centre for Remote Sensing) Convair-580 aircraft, in single and fully polarimetric modes and with different viewing geometry, were qualitatively and quantitatively evaluated by means of image interpretation and polarimetric analysis for their mapping potential over the densely forested study area. The airborne SAR data, supported with ancillary geoscience data sets and derivative topographic related products, have resulted in the availability of valuable and accurate terrain information such as topographic variations associated with the gently inclined recessive and resistant strata of the island succession. It also provided with information on the polarimetric scattering mechanism of the vegetation cover overlying the surface deposits and bedrock geology, suggesting a possible preferential distribution. With almost 50% of the Canadian territory covered by forest, radar remote sensing, as demonstrated by this study, is a cost-effective tool to produce more accurate regional structural and geological map in areas where traditional mapping campaigns failed due to the presence of an extensive vegetation cover.
Keywords: Geology.; Remote Sensing.